2011
DOI: 10.1186/1471-2458-11-92
|View full text |Cite
|
Sign up to set email alerts
|

Measuring adherence to antiretroviral therapy in northern Tanzania: feasibility and acceptability of the Medication Event Monitoring System

Abstract: BackgroundAn often-used tool to measure adherence to antiretroviral therapy (ART) is the Medication Event Monitoring System (MEMS), an electronic pill-cap that registers date and time of pill-bottle openings. Despite its strengths, MEMS-data can be compromised by inaccurate use and acceptability problems due to its design. These barriers remain, however, to be investigated in resource-limited settings. We evaluated the feasibility and acceptability of using MEMS-caps to monitor adherence among HIV-infected pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…Although microelectronic monitors may overestimate (individuals may open the bottle and not take the medication) or underestimate (individuals may remove more than one dose when they open the bottle) adherence (Bova et al, 2005), they have been shown to be more accurate than self-reported measures in both high and low income countries (Arnsten et al, 2001; Deschamps et al, 2004; Hugen et al, 2002; Lyimo et al, 2011; Vriesendorp et al, 2007). There are limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although microelectronic monitors may overestimate (individuals may open the bottle and not take the medication) or underestimate (individuals may remove more than one dose when they open the bottle) adherence (Bova et al, 2005), they have been shown to be more accurate than self-reported measures in both high and low income countries (Arnsten et al, 2001; Deschamps et al, 2004; Hugen et al, 2002; Lyimo et al, 2011; Vriesendorp et al, 2007). There are limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…First, if the individual's choice to continue using the EAM is voluntary, it is usually safe to assume that she genuinely wants to be more adherent, and thus, when she succeeds in doing so, that EAMs help her fulfill her own autonomous will. 10 This response is irrelevant in situations in which individuals choose to forgo therapy, such as therapy perceived to be futile or too toxic. One could also argue that what the EAM user Bloses^while using the EAM-primarily the freedom to remain sick or untreated-is of little objective value to the individual.…”
Section: Autonomymentioning
confidence: 99%
“…21 The extent to which someone tolerates loss of privacy or confidentiality is culturally and individually relative. 22 For instance, while HIV patients in India and Malawi 23 and in the United States 24 have expressed concerns that electronic pill bottles could raise suspicion from family and neighbors, such concerns were not raised by HIV patients in Uganda, 5 Tanzania, 10 or South Africa. 25 The heterogeneous findings of these studies may reflect variations in individual or cultural conceptualization of privacy and confidentiality, in criteria for what counts as a breach, or differences in disease-associated stigma.…”
Section: Privacy and Confidentialitymentioning
confidence: 99%
“…The emergence of HIV drug resistance mutations (DRMs) is influenced by many factors, foremost of which is adherence to antiretroviral therapy (ART) [2,3]. Adherence to ART can be measured by various methods [4], including MEM system [5], face-to-face interviews [2,3], self-reported adherence [6], review of pharmacy refill pick-ups, [7] and measuring blood or hair antiretroviral (ARV) levels [8]. It has long been accepted in clinical practice that an intermediate level of adherence at 70-89% is associated with higher risks of VF and detection of DRMs as compared with patients having high (≥90%) or low (< 70%) levels of cumulative adherence [2].…”
Section: Introductionmentioning
confidence: 99%